Probiotics in the prevention of ARVI - N. L. Kunelskaya; G. N. Izotova; T. P. Bessarab; M. V. Nagibina; Yu. V. Laryushkin (Медицинский совет, 2013)
ARVI is a short-term infection of the upper respiratory tract (including middle ear cavity and paranasal sinuses) which is caused by various respiratory viruses. According to the WHO [1], ARVI affects every third person every year. During epidemic outbreaks, 27.3 to 41.2 million cases are registered in Russia, of which 2 million are located in Moscow [2]. Despite a wide range of antiviral and symptomatic medications, the problem of treatment and prevention of ARVI is far from being finally solved. That's why medicines that strengthen the immunity of a macroorganism are becoming increasingly popular.